2011
DOI: 10.3382/ps.2011-01670
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different methods of molt: Production and welfare evaluation

Abstract: The purpose of this study was to evaluate alternative molting protocols assessing hen welfare and performance during and after molt. Hyline W-36 pullets were housed at 15 wk of age, and their egg production was obtained during this first cycle. When birds were 80 wk, the following molting treatments were applied: a conventional molt consisting of 10 d of fasting followed by cracked corn for 8 d and a pullet developer diet for 10 d; and 4 alternative molting programs: a soy hulls-based diet (12% CP, 1,455 kcal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…There is very limited literature about the performance, egg composition, egg solids, egg quality, and profits of postmolt hens (Wu et al, 2007), especially at long-term, a period near or exceeding to 100 weeks. An induced molting not only may improve performance and eggshell quality, but also increase profits by optimizing the use of replacement pullets on commercial layer farms (Lee, 1982;Barker et al, 1981;Bell, 2003;Mazzuco et al, 2011;Gongruttananun, 2018) proving the importance to understand its effect at long-term. Wilson et al (1967) studying several methods of inducing a molt and subsequent rest period, observed that molted hens present a better performance and shell thickness at short-term without affect the egg weight and albumen quality, regardless to the molt process used.…”
Section: Discussionmentioning
confidence: 99%
“…There is very limited literature about the performance, egg composition, egg solids, egg quality, and profits of postmolt hens (Wu et al, 2007), especially at long-term, a period near or exceeding to 100 weeks. An induced molting not only may improve performance and eggshell quality, but also increase profits by optimizing the use of replacement pullets on commercial layer farms (Lee, 1982;Barker et al, 1981;Bell, 2003;Mazzuco et al, 2011;Gongruttananun, 2018) proving the importance to understand its effect at long-term. Wilson et al (1967) studying several methods of inducing a molt and subsequent rest period, observed that molted hens present a better performance and shell thickness at short-term without affect the egg weight and albumen quality, regardless to the molt process used.…”
Section: Discussionmentioning
confidence: 99%
“…Selanjutnya data aktual produksi telur puyuh dianalisis dengan model regresi logistik. Model ini digunakan karena dapat mengevaluasi pengaruh perlakuan, umur dan interaksi antara keduanya (Mazzuco et al, 2011). Persamaan model regresi logistik (Ott, Longnecker, Taylor, & Payumo, 2010) yang digunakan adalah sebagai berikut:…”
Section: Manajemen Dan Analisis Dataunclassified
“…UU. y la UE ya han sido eliminadas (Mazzuco et al, 2011); prácticas que en México seguramente están próximas a ser suprimidas. Debido a que el ayuno prolongado no solo estimula la muda en las aves; además propicia incremento de enfermedades por la supresión del sistema inmune (Ricke, 2003), debido a que inducen una cascada de adaptaciones fisiológicas para restaurar la homeostasis; tal es el caso de la movilización de células del sistema inmunitario al torrente sanguíneo (Mumma et al, 2006), aumento de la proporción de heterófilos-linfocitos circulantes (Campo et al, 2008) y cambios en la etología de las aves (Dunkley et al, 2008).…”
Section: Introductionunclassified